The Impact of Artificial Intelligence in the Educational Field - Cristian VASILACHE, Petrut; Adrian TROACA, Victor; PARGARU, Ion; VATASE, Florin (European Journal of Sustainable Development, 2024)
Recently, the concept of Artificial Intelligence has caused concern not only in the scientific community but also in the media sphere, primarily due to the lack of a universally agreed-upon definition. There is a lack of consensus among people regarding a comprehensive definition of intelligence, and even more so regarding artificial intelligence. Given these circumstances, the growing prevalence of the notion of Intelligence Artificial intelligence has advanced to the extent that it is now a vital element in nearly every sector of today’s contemporary economy, exerting a substantial influence on our personal, societal, and political spheres. The foundation of this idea is based on the premise that human intelligence can be precisely described, allowing for the creation of a machine capable of simulating it. This gives rise to philosophical debates concerning the nature of consciousness and the moral implications of developing synthetic entities possessing human-like cognitive abilities. Artificial intelligence presents a myriad of challenges related to comprehension, responsibility, and confidence. Keywords: artificial intelligence, development, technology, education